Differences in anthropometric, somatotypological and components of body weight composition in teenager girls with primary dysmenorrhea - H.V. Chaika; D.G. Konkov; O.A. Taran; B.O. Markevych (Publishing House TRILIST, 2021)
Research aim was to identify differences in anthropometric, somatotypological and components of body weight between the respective groups of healthy teenager girls and patients with primary dysmenorrhea. Identifying such relationships will identify risk groups for primary dysmenorrhea and prevent its occurrence in adolescent girls. Materials and methods. All materials presented in the article are part of the dissertation "Prognosis, diagnosis and prevention of primary dysmenorrhea in patients of pubertal age with different somatotypes." Authors analyzed the indicators of 270 teenager girls, among which 200 persons were almost healthy and 70 patients with primary dysmenorrhea. For examination were used questionnaire-anamnestic method, measurement of anthropometric, somatotypological, components of body weight, ultrasound examination of the pelvic organs in two cycle phases and hormonal profile examination in the follicular and luteal phase of the menstrual cycle and statistical research methods. Results. Comparing anthropometric, somatotypological and components of body weight between the relevant (general or somatotype) groups of healthy girls and patients with primary dysmenorrhea, between the general group with primary dysmenorrhea and girls with primary dysmenorrhea of different somatotypes, as well as between patients with primary dysmenorrhea different somatotypes found significant differences (p <0.05) or tendencies of differences (p = 0.05) among total body size, body circumference, torso diameter, width of the distal epiphyses of the long tubular bones of the extremities, thickness of skin and fat folds, somatotype components, indicators of body weight composition. Conclusions. Medicine of the future will be preventive, aimed to identify predictors of pathology, factors influencing the development of nosology, and individual characteristics of teenage girls, which may lead to etiological and pathogenic impulse of clinical progression of primary dysmenorrhea. Therefore, the identification of prognostic markers of primary dysmenorrhea and formation of risk groups can improve not only life quality of a particular girl, but also the reproductive potential of nation.